Enabling digital growth through continuous education of project managers: a framework for collaborative, complementary, sustained, and simultaneous learning in software engineering organizations - Atanasijević, Srđan V.; Zahar, Monika N.; Rančić, Dejan D.; Vulić, Ivan B.; Atanasijević, Tatjana J. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: This paper introduces a novel PMO EDUCT framework that encompasses Collaborative, Complementary, Sustained, and Simultaneous learning explicitly tailored for the dynamic landscape of software engineering. This paper contributes to the ongoing discourse on education and professional development in the digital era by illuminating the challenges faced, the framework developed, and the measurable outcomes achieved. The presented framework underscores the need for agility, adaptability, and a relentless pursuit of knowledge as fundamental tenets for success in an ever-evolving landscape. Methods: Focusing on a large software engineering organization, this study explores the multifaceted aspects of project management education, methodology enhancement, and team optimization. The proposed methodology combines qualitative and quantitative approaches to explore the educational process area in a global organization and generate a flexible and measurable framework to improve corporate knowledge growth. The framework aims to provide learners the most flexibility about learning paths, schedules, collaboration, and best practice exchange while guaranteeing proper alignment with frequent market changes and emerging PM skills. Results: Findings indicate that personalised, continuous learning, facilitated through collaborative environments and custom-tailored content, yields significant benefits. Through analysis of key performance indicators (KPIs), this study showcases improved project onboarding, enhanced team collaboration, and the cultivation of a culture of innovation. Conclusion: This paper presents the PMO EDUCT framework that organizations can use to create a learning culture and empower their employees to succeed in the constantly evolving field of software development. By adopting collaborative, complementary, sustained, and simultaneous learning principles, organizations can develop a workforce with the essential skills of critical thinking, collaboration, and adaptability necessary for success in the digital era.